CUTANEOUS MELANOMA. CURRENT DIAGNOSTIC AND THERAPEUTIC GUIDELINES WITH COMPARISON OF POLISH AND INTERNATIONAL CLINICAL PRACTICE AND FUTURE PERSPECTIVES - Łuniewska, Wiktoria; Jabłoński, Maurycy; Kobaka , Laura; Chołast , Jakub; Kacer , Jakub; Kacer, Julia; Niepokój, Jakub; Jurga , Klaudia; Modrzyk, Marta (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives: Cutaneous melanoma is one of the most aggressive skin malignancies, characterized by a high potential for metastasis and a steadily increasing global incidence. While early-stage disease is associated with high cure rates, advanced melanoma has historically carried a poor prognosis, which has driven rapid advancements in both diagnostic technologies and systemic therapeutic strategies over the last decade.Aim: This narrative review aims to synthesize current international diagnostic and therapeutic guidelines (ESMO, NCCN, ASCO) and compare them with Polish clinical practice (PTOK), focusing on recent shifts in surgical management, the role of adjuvant therapies, and future perspectives in personalized medicine and artificial intelligence.Material and methods: The study is a narrative review based on the analysis of 21 recent peer-reviewed sources, including randomized controlled trials (RCTs), large-scale multicenter real-world studies from Poland, and the latest 2024 Clinical Practice Guidelines from the European Society for Medical Oncology and the National Comprehensive Cancer NetworkKey findings: International standards now emphasize a significant de-escalation of radical surgery, specifically recommending the omission of completion lymph node dissection (CLND) following a positive sentinel lymph node biopsy (SLNB) in favor of active ultrasound surveillance. Adjuvant systemic therapies including anti-PD-1 immunotherapy and targeted BRAF/MEK inhibitors have become the standard of care for high-risk patients, significantly improving relapse-free survival. Real-world data from Poland demonstrate a rapid alignment with these global trends, although challenges persist, as Polish patients are often diagnosed at more advanced stages, with a mean Breslow thickness of approximately 2.0 mm compared to